Pilar STBM pada Masyarakat di Wilayah Kerja UPTD Puskesmas Sei Lekop Bintan Timur Kabupaten Bintan - Fajar, Fajar; Razali, Roni; Syafariyah, Aida (PUAN INDONESIA, 2024)
Sanitation is an effort to control all human physical environmental factors that will cause things that are detrimental to physical development, health, and endurance. The limited sanitation of public facilities that meet environmental health requirements has not been optimal in the health center area has been observed. The method of activity that will be carried out together with the community service partners of the Health Center is an environmental health inspection activity. Based on the results of the community service activities that have been carried out, the following findings were obtained; of the 20 schools in the work area of the Sei Lekop Health Center UPTD that have undergone Environmental Health Inspections, only 1 school meets environmental health requirements and there are 19 schools that have not met environmental health requirements based on the results of environmental health infections carried out using the Environmental Health Infection form. There is already management of the Sei Lekop Health Center and schools in order to improve the Standards of Public Facilities (Schools). There is only a lack of advocacy for the parties above to improve these standards. Based on the results of community service, it is concluded that the Health Center partners need to improve environmental health inspection actions and there is advocacy from various parties involved in environmental health activities.Keywords: Sanitation, Environmental Health Inspection